Uniportal video-assisted thoracoscopic segmentectomy for fetal adenocarcinoma lung cancer with severe pulmonary emphysema: a case report - Wu, Yun-Sheng; Chen, Yu-Ting; Chuang, Jen-Hao; Liao, Hsien-Chi (Frontiers in Oncology, 2024)
Fetal adenocarcinoma is a very rare subtype of lung adenocarcinoma. Its incidence ranges from 0.1 to 0.87% among all primary lung neoplasms. Low-grade types tend to appear in the younger generation, and the age ranges from 20 to 50 years with a mean age of around 35 years. Surgical resection is currently the best way to treat fetal adenocarcinoma lung cancer without distant metastasis.This is a 56-year-old female who underwent low-dose computer tomography (LDCT) screening during the health examination. She used to be a heavy smoker for more than 30 years, and the CT images revealed severe bronchiectasis and emphysema. There is a solitary nodule with a diameter of 18.9 x 17.8mm in the central area of the left upper lobe. We decided to conduct left upper lobe S1~S3 segmentectomy under uniportal VATS. The surgery was successful, and the patient was discharged within one week and recovered well. The final diagnosis was fetal adenocarcinoma, lowgrade (pT1cN0Mx, stage IA3).The first case reported as fetal adenocarcinoma lung cancer who underwent uniportal video-assisted thoracoscopic segmentectomy. We believe it is a safe and feasible procedure for low-grade types fetal adenocarcinoma patient with poor pulmonary function.